2009
DOI: 10.1016/j.rmed.2008.12.014
|View full text |Cite
|
Sign up to set email alerts
|

Effects of arformoterol twice daily, tiotropium once daily, and their combination in patients with COPD

Abstract: In this study, the combination of nebulized arformoterol 15microg BID plus tiotropium 18microg DPI QD was the most effective in improving pulmonary function and disease symptoms. Mono-therapy improvement with arformoterol or tiotropium was similar. All three treatments were well tolerated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 64 publications
(49 citation statements)
references
References 47 publications
1
45
0
3
Order By: Relevance
“…All studies of tiotropium and formoterol/arformoterol combination therapy improved dyspnoea (assessed by the Transitional Dyspnoea Index (TDI)) to a greater extent than either monotherapy. 6,[15][16][17]19,20 Two further studies of tiotropium plus salmeterol (once or twice a day) also showed a marked improvement in dyspnoea with combination therapy over either monotherapy. 21,22 In a study by Aaron et al, 7 no significant difference in mean TDI total score was demonstrated between tiotropium plus salmeterol, tiotropium plus salmeterol/ fluticasone and tiotropium alone; however, it should be noted that a large number of patients discontinued during this study (61.0% completed), making it difficult to draw firm conclusions on efficacy between treatment groups.…”
Section: Dyspnoeamentioning
confidence: 95%
See 4 more Smart Citations
“…All studies of tiotropium and formoterol/arformoterol combination therapy improved dyspnoea (assessed by the Transitional Dyspnoea Index (TDI)) to a greater extent than either monotherapy. 6,[15][16][17]19,20 Two further studies of tiotropium plus salmeterol (once or twice a day) also showed a marked improvement in dyspnoea with combination therapy over either monotherapy. 21,22 In a study by Aaron et al, 7 no significant difference in mean TDI total score was demonstrated between tiotropium plus salmeterol, tiotropium plus salmeterol/ fluticasone and tiotropium alone; however, it should be noted that a large number of patients discontinued during this study (61.0% completed), making it difficult to draw firm conclusions on efficacy between treatment groups.…”
Section: Dyspnoeamentioning
confidence: 95%
“…Short-term (≤6 weeks) and longer-term (>12 weeks) studies demonstrated a decrease in rescue medication use with tiotropium and LABA (formoterol/arformoterol/salmeterol) combination therapy compared with either monotherapy, which may be associated with the improvements in symptoms observed with LABA/LAMA combination therapies in these studies. 2,8,15,17,[19][20][21][22][23] The reduction in rescue medication use in a 2-week and 6-week study of tiotropium plus formoterol compared with tiotropium is shown in Figure 2.…”
Section: Symptoms Symptom Scores and Rescue Medication Usementioning
confidence: 99%
See 3 more Smart Citations